A Systematic Review of Literature on Emerging Technologies and Specific Learning Difficulties - María Lozano-Álvarez; Sonia Rodríguez-Cano; Vanesa Delgado-Benito; Elvira Mercado-Val (MDPI AG, 2023)
Educational research on emerging technologies, particularly virtual reality and augmented reality, is expanding at the moment. The purpose of this contribution is to conduct a systematic review to understand the impact of emerging technologies in the educational and social-health fields. The PRISMA 2020 methodology was used to respond to the objective and research questions, ensuring the fulfillment of the quality criteria in the elaboration of the systematic review. This systematic review analyses the possible benefits that new technologies, specifically virtual reality and augmented reality, can have on learning difficulties such as dyslexia and ADHD disorder, as well as their inclusion in the social sphere. In this study, articles from both the health and educational fields will be reviewed. The research focuses on highlighting the incipient benefits of these new technologies for the aforementioned learning difficulties in the school and health fields. The main conclusions drawn show that research on these emerging technologies is still scarce and incipient in the educational field, with the main results found in the healthcare field.